The Influence of Islamic Economic Education Values on the Development of the Modern Economic System for Sustainable Development in Samarinda - Suwoko, Suwoko; Musyrifin, Ilmi Mu’min (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
This study aims to examine the extent to which the values of Islamic economic education influence the development of MSMEs within the modern economic system to achieve sustainable development in Samarinda City. The method employed is descriptive qualitative with content analysis of secondary data obtained through a review of national scientific journals, news reports, and data from the Central Statistics Agency. The results show that the internalization of the values of honesty, justice, responsibility, and sustainability in MSME practices enhances competitiveness, innovation, and digital inclusion, thereby supporting sustainable local economic growth. The synergistic interaction between Islamic economic education, government support, and digitalization encourages Samarinda's MSMEs to transform into resilient modern business actors. Recommendations are made for policymakers to strengthen the Islamic economics curriculum, expand access to sharia financing, and accelerate digitalization and halal certification as instruments for sustainability.